Isolated Malay speech recognition using fuzzy logic - Normiza, Mohd Yusof (2019)
Artificial intelligence (AI) is one of the method that human use to communicate between human and computer. There are a lot of applications has been produces by AI approach such as medical diagnosis, proving mathematical theorems and autonomous vehicle. Many methods and approach has been used by researcher to develop speech recognition system such as neural network and Hidden Markov Model. This research aim is to develop a isolated Malay speech recognition using Fuzzy Logic method. This research is focused on six isolated words which is empat (four), lapan (eight), rekod (record), tidak (no), tujuh (seven), and tutup (close). This research is also focused on the development of fuzzy rules between each words. The evaluation process is measured based on the accuracy rate between the previous method using Hidden Markov Model. The result show that 75% speech recognition accuracy rate using fuzzy logic method.